Contact Allergy to Ingredients of Hair Cosmetics Associated with Occupational and Non-Occupational Exposure—Trends from 1995 to 2020 in Central Europe, with or without Regulation - Uter, Wolfgang; Schwensen, Jakob Ferløv Baselius; Blömeke, Brunhilde; Gefeller, Olaf; John, Swen M.; Bieck, Cara; Schubert, Steffen (Contact Dermatitis, 2026)
Background: Hair cosmetic products contain various chemicals which are partly potent contact sensitizers. These may cause occupational hand eczema in hairdressers, but also scalp and face dermatitis in consumers. Objective: To (i) highlight differences between the spectrum of occupational and non-occupational exposure reflected in sensitization, and (ii) correlate trends in the last decades with regulatory interventions (or the lack thereof). Methods: Patch test and clinical data collected by the IVDK (https://www.ivdk.org) between 01/1995 and 12/2020 were subjected to a pooled re-analysis. Age-stratified sensitization prevalences in female hairdressers and consumers, respectively, were calculated for 2-yearly intervals spanning the study period. Log-binomial regression models were employed to estimate the association between contact allergy and (i) subgroup (hairdresser vs. consumer), (ii) a 3-level age category, and/or (iii) time period, respectively. Results: Hair dyes were the most frequent sensitizers in hairdressers and consumers; however, there was a marked increase in (particularly the young) consumers. Pyrogallol had been banned in 1992 but still elicited positive patch test reactions even in the young. Hydroquinone, banned in 2013 in dyes, showed no decline in sensitization prevalence. Glyceryl thioglycolate has been withdrawn and later banned in Germany since around 1995, which caused contact allergy prevalence to drop to almost zero in the youngest age group, largely until today. Conclusion: As a limitation, putatively differing selection for patch testing render prevalences difficult to compare between hairdressers and consumers. The importance of hair dye allergy is evident, needing continued efforts to increase product safety from the manufacturing and regulatory side. The potential of (self-)regulatory intervention is well illustrated by the decline of contact allergy to glyceryl thioglycolate.
CRIS-Team Scopus Importer:2026-01-09
Keywords: clinical epidemiology; contact allergy; hair cosmetics; hairdressers; regulation; RRID:SCR_001905; surveillance